Hierarchical WO3/TiO2 nanotube nanocomposites for efficient photocathodic protection of 304 stainless steel under visible light - Sun, Weixiang; Cui, Siwen; Wei, Ning; Chen, Shougang; Liu, Yupeng; Wang, Daoai (Journal of alloys and compounds, 2018)
A new photoanode of hierarchical WO3 and TiO2 nanotube arrays with a layered composite structure is prepared through in situ deposition of WO3 into TiO2 nanotubes by one-pot hydrothermal method. Photo-induced open circuit potential, photocurrent density, electrochemical impedance spectroscopy, and Tafel curves are measured under visible light to evaluate the photoelectrochemistry properties and the photocathodic protection effect of the composite photoelectrode. The result showed that compared with the hierarchical WO3 deposited on bare Ti substrate, the photocurrent density of WO3/TiO2/Ti with the thin TiO2 nanotube arrays as the transition layer increased from 0.072 mA/cm2 to 2.5 mA/cm2. Moreover, as for the photocathodic protection application, the photo-induced open circuit potential drop of the nanocomposite photoanode was about 260 mV and the charge transfer resistance was reduced by 106 times, indicating the efficient photogenerated cathode protection of the coupled metals under visible light illumination. [Display omitted] •3D hierarchical WO3/ TiO2 NTs composite photoelectrode is successfully prepared.•The two-step synthetic route is facile and feasible.•The photo-induced open circuit potential of composite shows a negative shift.•TiO2/WO3 electrodes show effective photocathodic protection effect even in the dark.